2023
DOI: 10.1111/1365-2745.14207
|View full text |Cite
|
Sign up to set email alerts
|

Root litter decomposition is suppressed in species mixtures and in the presence of living roots

Cristina Heredia‐Acuña,
Marina Semchenko,
Franciska T. De Vries

Abstract: Plant species diversity and identity can significantly modify litter decomposition, but the underlying mechanisms remain elusive, particularly for root litter. Here, we aimed to disentangle the mechanisms by which plant species diversity alters root litter decomposition. We hypothesised that (1) interactions between species in mixed communities result in litter that decomposes faster than litter produced in monocultures; (2) litter decomposition is accelerated in the presence of living plants, especially when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…In addition, the rhizosphere effect led to an enrichment of the Fusarium genus, which is a primary pathogen responsible for causing root rot in wheat [ 63 ]. The above root-indued changes in KSDMs indicate that the presence of plant roots has a negative effect on straw decomposition [ 19 , 64 , 65 ] and that straw return may also cause some plant root diseases [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the rhizosphere effect led to an enrichment of the Fusarium genus, which is a primary pathogen responsible for causing root rot in wheat [ 63 ]. The above root-indued changes in KSDMs indicate that the presence of plant roots has a negative effect on straw decomposition [ 19 , 64 , 65 ] and that straw return may also cause some plant root diseases [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biogeochemical cycling mediated by microbes within this interface is distinctive [ 18 ]. Heredia-Acuña et al [ 19 ] found that the presence of living roots decreased the cumulative decomposition rate of root litter in a greenhouse simulation experiment. However, previous studies of straw decomposition in agricultural ecosystems have paid little attention to this interface.…”
Section: Introductionmentioning
confidence: 99%
“…Through correlation analysis, a noteworthy negative correlation between soil organic carbon and vegetation biomass carbon was identified in the Yellow River Delta. This observation could be attributed to a complex interplay of factors in the Yellow River Delta [66], including poor soil retention, prolonged exposure to flowing water, and human disturbance [20,31]. These factors collectively influence soil organism activity and the decomposition rate of litter, resulting in decreased stability and accumulation of litter carbon in the soil [67].…”
Section: The Impact Of Vegetation Biomass Carbon On Biodiversity In T...mentioning
confidence: 99%